A Dual-Band Metamaterial Design using Double SRR Structures - Liu, Jian-Chao; Shao, Wei; Wang, Bing-Zhong (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Based on a periodic array of interspaced conducting split ring resonators (SRRs) and continuous wires, a composite structure is proposed to hold a dual-band in the microwave regime. With simultaneously negative values of effective permeability and permittivity, the composite structure displays a negative refractive index characteristic in a dual-band. The location of the two resonant frequencies is investigated by adjusting the distance between the neighboring asymmetrical SRRs in a single array element. Numerical results show the impact of the distance on the resonant frequencies due to coupling effects. Different simulation softwares are adopted to verify the accuracy of our design.